Rancangan Sistem Pakar Pemilihan Program Studi Untuk Calon Mahasiswa Baru (dengan studi kasus di IAIN Raden Fatah Palembang) - Ruliansyah Ruliansyah (Wardah, 2011)
Expert systems are one branch of artificial intelligence that uses knowledge-specific knowledge possessed by an expert to solve a specific problem by using an intelligent computer program. One example of the use of expert systems is to choose a course of study in universities in IAIN Raden Fatah Palembang. Expected with this expert system can help prospective students to choose courses that fit with the capabilities they have. Prospective students can conduct a question and answer with a system (software) that eventually software will give the course a decision that suits them. This system not only receives the answer "yes" and "no", but with the provision of the trust, which is expected to provide a better level of confidence.